2007
DOI: 10.1017/s0022029906002275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding two levels of propionibacteria to dairy cows on plasma hormones and metabolites

Abstract: To determine the effect of feeding propionibacteria on metabolic indicators during lactation, multiparous and primiparous Holstein cows were fed one of three dietary treatments in a 2 x 3 factorial design from 2 weeks prepartum to 30 weeks post partum: (1) Control (primiparous n=5, multiparous n=8) fed a total mixed ration (TMR); (2) high-dose group (primiparous n=6, multiparous n=5) fed TMR plus 6 x 10 (11) cfu/head daily (high-dose P169) of propionibacterium strain P169; or (3) low-dose group (primiparous n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
17
2
Order By: Relevance
“…One particular strain, Propionibacterium acidipropionici P169, is marketed as a commercial supplement for dairy cattle to reduce the incidents of sub-acute acidosis. Supplementing P169 to Holstein dairy cattle increased ruminal propionate, milk production (Stein et al, 2006;Aleman et al, 2007;Weiss et al, 2008), milk solids, but reduced milk fat (Lehloenya et al, 2008a). In addition, Lehloenya et al (2008b) reported that P169 increased propionate which led to a reduction in the acetate:propionate (A:P) ratio in steers fed a sorghum silage-based diet.…”
Section: Introductionmentioning
confidence: 95%
“…One particular strain, Propionibacterium acidipropionici P169, is marketed as a commercial supplement for dairy cattle to reduce the incidents of sub-acute acidosis. Supplementing P169 to Holstein dairy cattle increased ruminal propionate, milk production (Stein et al, 2006;Aleman et al, 2007;Weiss et al, 2008), milk solids, but reduced milk fat (Lehloenya et al, 2008a). In addition, Lehloenya et al (2008b) reported that P169 increased propionate which led to a reduction in the acetate:propionate (A:P) ratio in steers fed a sorghum silage-based diet.…”
Section: Introductionmentioning
confidence: 95%
“…They have been used as a DFM for ruminants in the past to improve energy metabolism and increase milk production (Stein et al, 2006;Aleman et al, 2007), weight gain, and feed efficiency (Swinney-Floyd et al, 1999;Lehloenya et al, 2008), and decrease the incidence of acidosis (Parrott et al, 1997;Ghorbani et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Estimates by Seal and Reynolds (1993) indicate that propionate supplies 32–73% of glucose demands. Although feeding Propionibacteria strain 169 (P169) to Holstein dairy cows alters metabolism (Francisco et al., 2002; Aleman et al., 2007) and increases milk production (Stein et al., 2006), the acute temporal effect of feeding P169 on insulin and glucose secretion have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%